What is True Art or Good Art? - Daniel Shorkend (RIRAI Publisher, 2022)
In this brief account I argue that art ought to be an enterprise wherein the artist tries to understand his/her process and develop a discursive understanding annexed to or in tandem with practice. I argue that innovation in art – the claims of the great artists – resulted in a certain paradigm shift. Yet the postmodern move towards a largely anti-intellectual polarity does a great disservice to art. I conclude with the necessity to at least define our terms, otherwise the possibility of art even carrying some sense evaporates, let alone any meaningful discrimination.